Ubiquitination of CD47 Regulates Innate Anti‐Tumor Immune Response - Qian Gou; Bingjun Yan; Yalan Duan; Yilei Guo; Jing Qian; Juanjuan Shi; Yongzhong Hou (Advanced Science)
Abstract In addition to adaptive immune checkpoint of PD‐1/PD‐L1, the innate immune checkpoint SIRPα/CD47 plays an important role in regulation of tumor immune escape. However, the mechanism of CD47 ubiquitination on tumor immune escape remains unclear. Here it is found that TRAF2 bound to the C‐terminal of CD47 cytoplasmic fragment and induced its ubiquitination, leading to inhibition of CD47 autophagic degradation by disrupting its binding to LC3, which in turn inhibited macrophage phagocytosis and promoted tumor immune escape. In contrast, loss of TRAF2 facilitated CD47 autophagic degradation and inhibited tumor immune escape. Moreover, autophagy induction promoted CD47 degradation and enhanced the efficacy of CD47 antibody anti‐tumor immunotherapy. These findings revealed a novel mechanism of ubiquitination of CD47 on tumor immune escape.